La Novela Ecuatoriana - Moyano, Bolivar (Revista Universidad de Guayaquil, 1998)
If any of our works—devoted to criticism, within the context of literary essay—deserves the label of "Classic," it is The Ecuadorian Novel by Ángel F. Rojas.It was published in 1948 (half a century ago), as number 34 in the “Tierra Firme” collection, by the Fondo de Cultura Económica (Mexico).The same publishing house, during those years, also published other landmark works of our literature: Ecuador: Drama and Paradox, The Argonauts of the Jungle (Leopoldo Benítez Vinueza), and Ecuadorian Visual Arts (José G. Navarro).